Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt A = ( - 7 .x2 . y3 ) . ( - 3.x3 . y5 )
Ta có : A = ( - 7 .x2 . y3 ) . ( - 3.x3 . y5 )
= ( - 7 ) . ( - 3 ) . x2 .x3 .y3 . y5
= 21.x5 . y8
= [ -7 . ( - 3 ) ] ( x2 . x3 ) ( y3 y5 )
= 21 x5 y8
\(a,\left(3x+5\right)^2+\left(3x-5\right)^2-\left(3x+2\right)\left(3x-2\right)=9x^2+30x+25+9x^2-30x+25-9x^2+4=9x^2+54\)
\(b,BT=2x\left(4x^2-4x+1\right)-3x\left(x^2-9\right)-4x\left(x^2+2x+1\right)=8x^3-8x^2+2x-3x^3+27x-4x^3-8x^2-4x=x^3-16x^2+25x\)
\(c,BT=\left(x+y-z\right)^2-2\left(x+y-z\right)\left(x+y\right)+\left(x+y\right)^2=\left(x+y-z-x-y\right)^2=z^2\)
Ta có : \(\left|3x-1\right|=3x-1\) với \(3x-1\ge0\Leftrightarrow3x\ge1\Leftrightarrow x\ge\frac{1}{3}\)
\(\left|3x-1\right|=-3x+1\)với \(3x-1< 0\Leftrightarrow3x< 1\Leftrightarrow x< \frac{1}{3}\)
Suy ra : Với : \(x\ge\frac{1}{3}\)thì \(B=3x-1+12x-1=15x-2\)
Với : \(x< \frac{1}{3}\)thì \(B=-3x+1+12x-1=9x\)
\(M+N+P=2x^2-3x+1+5x^2+x+x^2-4\)
\(=8x^2-2x-3\)
... Đúng thì ủng hộ nha ...
Kết bạn với tớ ... ;) ;)
\(M+N+P=2x^2-3x+1+5x^2+x+x^2-4\)
\(=\left(2x^2+5x^2+x^2\right)+\left(x-3x\right)+\left(1-4\right)\)
\(=8x^2-2x-3\)